2006
DOI: 10.1096/fj.05-4943fje
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of anandamide levels as an endogenous mechanism and a pharmacological strategy to limit colon inflammation

Abstract: Direct stimulation of cannabinoid CB1 receptors exerts a protective function in animal models of inflammatory bowel diseases (IBDs). However, it is not known whether endocannabinoids are up-regulated during IBDs in animals or humans, nor whether pharmacological elevation of endocannabinoid levels can be exploited therapeutically in these disorders. In this study we addressed these questions. Colon inflammation was induced in mice and rats with 2,4-dinitrobenzene- and 2,4,6-trinitrobenzene sulfonic acids (DNBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
198
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(217 citation statements)
references
References 39 publications
15
198
2
2
Order By: Relevance
“…FAAH can also degrade 2-AG in vitro , 7,13 yet variations of its activity observed in IBD mucosa did not exert any effect on 2-AG levels. Our results are in agreement with the observation of Marquez et al , 21 who found lower NAPE-PLD expression and high AEA levels in inflamed ulcerative colitis when compared with control mucosa, but they diverge from those by D ' Argenio et al 22 Moreover, the findings of Marquez et al , 21 who showed the lack of difference in the diacylglycerol lipase / monoacylglycerol lipase ratio between ulcerative colitis patient and healthy control epithelium, support our data on mucosal 2-AG levels.…”
Section: Articlessupporting
confidence: 91%
“…FAAH can also degrade 2-AG in vitro , 7,13 yet variations of its activity observed in IBD mucosa did not exert any effect on 2-AG levels. Our results are in agreement with the observation of Marquez et al , 21 who found lower NAPE-PLD expression and high AEA levels in inflamed ulcerative colitis when compared with control mucosa, but they diverge from those by D ' Argenio et al 22 Moreover, the findings of Marquez et al , 21 who showed the lack of difference in the diacylglycerol lipase / monoacylglycerol lipase ratio between ulcerative colitis patient and healthy control epithelium, support our data on mucosal 2-AG levels.…”
Section: Articlessupporting
confidence: 91%
“…Indeed, anandamide and N-palmitoylethanolamine levels are altered in colon mucosal biopsies of patients with ulcerative colitis (UC) or Crohn's disease (CD), especially during acute flares, with no change in 2-arachidonoylglycerol levels [35,52,53] (changes in the ECS in human IBD are summarized in Table 1). NAE levels were reported to be either increased or decreased depending on the study.…”
Section: Box 2 the Ecs Toolboxmentioning
confidence: 99%
“…3 Recent evidence suggests a role for the cannabinoid system in IBD regulation. Cannabinoid receptors 1 and 2 (CB1 and CB2) are expressed in normal human colon 4,5 and are up-regulated in IBD colonic tissue. In addition, an enhanced level of endocannabinoids was found in biopsy specimens from patients with ulcerative colitis.…”
mentioning
confidence: 99%
“…In addition, an enhanced level of endocannabinoids was found in biopsy specimens from patients with ulcerative colitis. 5 It is thought that CB1 activation results in a decrease of intestinal hypermotility and hypersecretion, whereas the activation of CB2 results in the inhibition of proinflammatory mediators. In addition, both CB2 and CB1 knockout mice are more susceptible to the development of experimental colitis, and the activation of these receptors is extremely important for the abrogation of intestinal inflammation.…”
mentioning
confidence: 99%